Humanistic Governance in Islamic Religious Education: Internalizing Child-Friendly Values to Create Violence-Free Primary Schools - Sirajuddin, Sirajuddin; Zamroni, Zamroni; Bahrani, Bahrani (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the internalization of Child-Friendly values in Islamic Religious Education instruction in elementary schools in East Kalimantan, emphasizing the humanistic educational governance aspect as part of Islamic educational management. This study uses a qualitative approach with a multi-site study design. Data were collected through observation, in-depth interviews, and documentation studies. The data analysis technique in this study follows the interactive model of Miles and Huberman, which involves three stages: data condensation, data presentation, and conclusion drawing. The results show that the process of internalizing Child-Friendly values is carried out through three stages: value transformation, value transaction, and value internalization. The habitualization of values through religious and social activities such as congregational prayer and joint tadarus, along with the involvement of parents and the community, has proven effective in creating a child-friendly school culture. The implications of this study highlight the importance of integrating educational governance grounded in humanistic values into educational management, where all relevant parties, including teachers and parents, play a role in creating a safe, inclusive educational environment that supports the holistic development of students’ character.